Th1 cells reduce the osteoblast-like phenotype in valvular interstitial cells by inhibiting NLRP3 inflammasome activation in macrophages - Jing Lu; Jiaming meng; Gang Wu; Wulong Wei; Huabao Xie; Yanli Liu (BMC, 2024)
Abstract Background and aims Inflammation is initiates the propagation phase of aortic valve calcification. The activation of NLRP3 signaling in macrophages plays a crucial role in the progression of calcific aortic valve stenosis (CAVS). IFN-γ regulates NLRP3 activity in macrophages. This study aimed to explore the mechanism of IFN-γ regulation and its impact on CAVS progression and valve interstitial cell transdifferentiation. Methods and results The number of Th1 cells and the expression of IFN-γ and STAT1 in the aortic valve, spleen and peripheral blood increased significantly as CAVS progressed. To explore the mechanisms underlying the roles of Th1 cells and IFN-γ, we treated CAVS mice with IFN-γ-AAV9 or an anti-IFN-γ neutralizing antibody. While IFN-γ promoted aortic valve calcification and dysfunction, it significantly decreased NLRP3 signaling in splenic macrophages and Ly6C+ monocytes. In vitro coculture showed that Th1 cells inhibited NLPR3 activation in ox-LDL-treated macrophages through the IFN-γR1/IFN-γR2-STAT1 pathway. Compared with untreated medium, conditioned medium from Th1-treated bone marrow-derived macrophages reduced the osteogenic calcification of valvular interstitial cells. Conclusion Inhibition of the NLRP3 inflammasome by Th1 cells protects against valvular interstitial cell calcification as a negative feedback mechanism of adaptive immunity toward innate immunity. This study provides a precision medicine strategy for CAVS based on the targeting of anti-inflammatory mechanisms. Graphical Abstract